PERBEDAAN USAHATANI PADI SISTEM JAJAR LEGOWO DENGAN SISTEM TEGEL DI DESA TAMBAK SARINAH KABUPATEN TANAH LAUT - Eddy Triatmoko; Subhan Fitriadi; Fenny Refiana; Sondang Pohan (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2018)
The purpose of this research is to know the revenue,the total cost,income and Comparasion of farming padi jajar legowo system with tegel system . This research was conducted in Pebruari to April 2018 at village tambak sarinah tanah laut regency. The puposive sampling methode used was by observing 16 farmers in  village tambak sarinah who planted padi Jajar legowo system and 16 farmers Planted Padi Tegel system . The Average result  Padi jajar legowo system of the revenue is Rp. 22.751.250,-/ farmer, the average eksplicit cost is Rp. Rp 12.243.089/farmer, and income is Rp10.501.912/farmer.. and  Average result  Padi Tegel system of the revenue is Rp. Rp 22.537.500,-/ farmer, the average eksplicit cost is Rp. Rp 13.659.779 /farmer, and income is RpRp 7.097.096/farmer. The Income comparasion effect jajar legowo system is very significant to farming tegel system,  based on result  t student  95 % α = 0,05  (1,3322 < 2.042) . From  this result of development  we believe that this farming Padi Jajar legowo sistem has good prospect and revenue, tecnically and economically.